(untitled) (Contemporary Mathematics, 2021)
Security of some present day public key cryptosystem (PKC) is based on general linear groups as it is a good choice for developing such types of cryptosystems. This study presents various public key encryption schemes based on general linear groups. Different techniques including automorphisms in connection with conjugacy search problem and its generalization are used to develop these schemes. Further, the grouprings are chosen as a platform to enhance the security and efficiency. Numerous aspects related to our new proposal are also elaborated.